Effects of Water Pollution on Human Health and Disease Heterogeneity: A Review - Lin, Li; Yang, Haoran; Xu, Xiaocang (Frontiers in Environmental Science, 2022)
Background: More than 80% of sewage generated by human activities is discharged into rivers and oceans without any treatment, resulting in environmental pollution and more than 50 diseases. 80% of diseases and 50% of child deaths worldwide are related to poor water quality. Methods: This paper searched the SCI/SSCI index papers in Google Academic, and selected 49 relevant papers finally based on the keywords of water pollution, water quality, health, cancer, and so on. Results: The impact of water pollution on human health is significant, although there may be regional, age, gender, and other differences in degree. The most common disease caused by water pollution is diarrhea, which is mainly transmitted by enteroviruses in the aquatic environment. Discussion: Governments should strengthen water intervention management and carry out intervention measures to improve water quality and reduce water pollution's impact on human health.